Perbandingan Biaya Distribusi Produk Cat Menggunakan Model Transportasi Metode Vogel’s Approximation Method dan Least Cost - Fyoni Erza; Fahriza Nurul Azizah (Engineering Faculty at Universitas Singaperbangsa Karawang, 2023)
This research was conducted at PT Victorindo Kimiatama, a company that distributes paint and coating products in the Jabodetabek area and its surroundings where this company does not yet have a permanent distribution cost optimization calculation technique that can result in increased distribution costs. This study aims to determine efficient distribution channels and minimize distribution costs. The distribution cost calculation applies the transportation model by comparing the VAM and least cost methods. The calculation results show that there is a difference in the total cost of distribution where the VAM method produces a cost of Rp. 795,161.21 while the least cost method is Rp. 735,824.48, so that by using the least cost method the company can save distribution costs of Rp. 747,300.52 or 0.49% of the previous distribution fee